Heterogeneous catalyst based on tourmaline composite material, its preparation and application

By preparing CuMoO4/MnO2/tourism heterogeneous catalyst, combined with the surface electric field and spontaneous polarization effect of tourmaline, the photocatalytic activity of CuMoO4 and the narrow band gap characteristics of MnO2 are used to form a heterojunction matching the band gap structure, and coordinately activate PMS to generate strong oxidation radicals, solving the problems of poor response to visible light and low activation performance of PMS, achieving efficient pollutant degradation effect.

CN117085695BActive Publication Date: 2025-07-18CHINA UNIV OF MINING & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311065687.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-07-18
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

The existing photocatalysts have poor responsiveness to visible light, low activation performance of PMS, resulting in low pollutant degradation efficiency, and traditional catalysts have problems such as secondary pollution and insufficient activation capacity.

Method used

By preparing CuMoO4/MnO2/Travel heterocatalyst, combining the surface electric field and spontaneous polarization effect of Tourmaline, the photocatalytic activity of CuMoO4 and the narrow band gap characteristics of MnO2 are used to form a heterojunction matching the band gap structure, and the PMS is activated in concert to generate strong oxidation radicals to achieve a photo-Fenton reaction.

Benefits of technology

The degradation efficiency of pollutants was significantly improved in visible light irradiation and PMS activation systems, especially the removal rate of tetracycline hydrochloride reached 93.48%, broadening the treatment ideas in the field of water purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117085695B_ABST
    Figure CN117085695B_ABST
Patent Text Reader

Abstract

The present invention discloses a heterogeneous catalyst based on tourmaline composite material and its preparation and application, belonging to the fields of inorganic nanomaterials and environment. In this application, a CMT heterogeneous catalyst is prepared by compounding copper molybdate, manganese dioxide and tourmaline. Tourmaline can be used as a Fenton-like reagent to activate PMS to promote the generation of reactive free radicals. Copper molybdate and manganese dioxide have excellent photocatalytic activity. Based on this, the prepared composite material can produce a synergistic effect in the visible light irradiation and PMS activation system; by reasonably compounding copper molybdate with wide / narrow band gaps and manganese dioxide coupling, a CMT heterojunction with a matching band gap structure is prepared, and the light absorption threshold and energy band structure of the photocatalyst are effectively adjusted, improving the mobility of photo-generated carriers and reducing the recombination of photo-generated electrons and holes, and enhancing the photocatalytic activity of the semiconductor material; using this catalyst to degrade water pollutants, the removal rate of 50 mg / L of tetracycline hydrochloride reaches 93.48%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of inorganic nanomaterials and the environment, and particularly to a heterogeneous catalyst based on a tourmaline composite material, and its preparation and application. Background Art

[0002] As a class of broad-spectrum antibacterial drugs, antibiotics have been widely used in the treatment of infectious diseases in humans and animals. However, the abuse of antibiotics may lead to the problem of drug resistance in organisms, accelerate the spread of drug-resistant genes and drug-resistant bacteria, and cause serious harm to the ecological environment and human health. At present, the methods for treating pollutants in wastewater mainly include physical adsorption, bioremediation, chemical oxidation, etc. Although physical adsorption can remove pollutants to a certain extent, it only transfers organic pollutants from one phase to another new phase and cannot fundamentally achieve the degradation of pollutants. Bioremediation does not require the introduction of chemical agents and has the characteristics of environmental protection, but the repair cycle is long and the repair effect on high-concentration polluted wastewater is poor. How to efficiently degrade organic pollutants in wastewater has become a key technical problem to be solved in the field of environmental science.

[0003] Advanced oxidation technology can generate highly reactive free radicals with strong oxidation ability through chemical methods, thereby attacking organic pollutant molecules to achieve the degradation and mineralization of pollutants. It has the advantages of low repair cost, complete degradation, etc., and has great application potential in the field of organic pollutant degradation. For example, the new persulfate advanced oxidation technology has stronger oxidation ability. The redox potential of the sulfate radical (SO4 ·- ) generated after the activation of persulfate is 2.5-3.1V, which is higher than the redox potential of ·OH (1.8-2.7V). SO4 ·- has a fast reaction rate, a wide application range, mild reaction conditions, and a high mineralization rate for organic pollutants. Persulfates that can catalytically activate to generate SO4 ·- include peroxymonosulfate (PMS) and peroxydisulfate (PDS). At present, the catalysts for activating PMS and PDS are mainly homogeneous Fe ions and their heterogeneous oxides. These catalysts often have problems such as secondary pollution, uneven active sites, insufficient activation ability, and unclear structure-activity relationship. Therefore, it is necessary to seek new, highly efficient and pollution-free catalytic materials for activating persulfate to generate SO4 ·- .

[0004] Tourmaline is a cyclic structure borosilicate mineral containing multiple elements such as B, Al, Na, Fe, Mg, Li, etc., and its chemical formula is XY3Z6Si6O 18 (BO3)3W4, where X = K + , Na + , Ca2+ or a vacancy, Y = Mg 2+ , Fe 3+ , Al 3+ , Cr 3+ , V 3+ , Ti 4+ , Z = Al 3+ , Fe 3+ , Mg 2+ , Cr 3+ , V 3+ , Fe 2+ , W = OH - , O - , F - , which has been proven to have a dual role in the photo - like Fenton system for wastewater purification. On the one hand, tourmaline, as a borosilicate mineral with unique properties such as surface electric field, spontaneous polarization effect, and negative ion release property, can improve the catalytic activity of the composite photocatalytic material by inhibiting the recombination of carriers in the photocatalyst. The electric field generated by tourmaline is about 10 4 ~10 7 Vm -1 , which can greatly promote the adsorption of pollutants on the catalyst surface, thereby enhancing the photocatalytic degradation of pollutants. On the other hand, tourmaline can act as a Fenton - like reagent, generating free radicals with strong oxidation ability by activating PMS, and thus can effectively remove pollutants.

[0005] Transition metal molybdates have also attracted great attention of researchers in this field due to their special structures, excellent proton conductivity, and catalytic properties. Combining molybdates with tourmaline can obtain a new type of natural mineral - based visible - light photocatalyst. For example, a composite photocatalyst of bismuth molybdate coated on tourmaline disclosed in Chinese Patent CN 111450822 A forms a good coating on the surface of tourmaline. This catalyst has visible - light photocatalytic performance and can be used for the degradation of organic wastewater. However, it is unknown whether a heterogeneous photo - like Fenton system with efficient photocatalysis and persulfate activation synergistic effect can be constructed based on this catalytic material, and the band - gap width of bismuth molybdate is 2.8 eV, with a relatively wide band - gap and a narrow light absorption range, which will reduce the utilization efficiency of visible light.

[0006] Manganese dioxide (MnO2), as a typical manganese - based material, has been widely used in the field of wastewater treatment due to its excellent chemical stability and catalytic activity. Different from molybdates, MnO2 has a relatively narrow band - gap, about 1 - 2 eV, and a high photo - quantum efficiency, thus having a strong visible - light absorption ability. However, the recombination rate of photo - generated carriers of this type of material is relatively high, so the application of pure MnO2 in photocatalysis is also limited.

[0007] In summary, if the metal molybdate, MnO2 and tourmaline can be triple-compounded, by limiting the raw material ratio, the band gap characteristics and electron-hole recombination characteristics of the two materials of metal molybdate and MnO2 can be better integrated, the respective advantages of the two materials can be synergistically exerted, and a new composite catalytic material can be prepared relying on the excellent carrier material of tourmaline, which will undoubtedly play a good promoting role in the degradation of organic pollutants in water by the photo-Fenton-like reaction. Furthermore, it can provide an efficient, environmentally friendly and low-cost pollutant degradation strategy for water pollution treatment, bringing new ideas and new solutions for water purification. Summary of the Invention

[0008] The purpose of the present invention is to solve the problems of poor visible light responsiveness and low PMS activation performance of the photocatalysts disclosed in the prior art, and to provide a heterogeneous catalyst based on tourmaline composite materials and its preparation and application. The preparation process of the CMT heterogeneous catalyst is simple and the operation is safe. This heterogeneous catalyst has excellent photo-Fenton-like catalytic activity and can produce a synergistic effect in the visible light irradiation and PMS activation system.

[0009] The technical solution of the present invention is: a preparation method of a heterogeneous catalyst based on tourmaline composite materials, comprising the following steps:

[0010] 1) Weigh KMnO4 and tourmaline and disperse them in deionized water. After ultrasonic treatment and stirring, a suspension A is obtained;

[0011] 2) Transfer the suspension A obtained in step 1) to a reaction kettle for hydrothermal reaction;

[0012] 3) Centrifuge the product obtained in step 2), wash it, and obtain a brownish-black precipitate;

[0013] 4) Dry the precipitate obtained in step 3). After cooling to room temperature, the obtained brownish-black powder is the MnO2 / tourmaline composite catalyst;

[0014] 5) Weigh Cu(NO3)2·3H2O and (NH4)6·Mo7O 24 ·4H2O and dissolve them in deionized water, and stir to obtain a solution B; weigh the MnO2 / tourmaline composite and disperse it in the solution B, and stir to obtain a suspension C;

[0015] 6) Transfer the suspension C to a reaction kettle for hydrothermal reaction;

[0016] 7) Centrifuge the product obtained in step 6), wash it, and obtain a brown precipitate;

[0017] 8) Dry the brown precipitate obtained in step 7). After cooling to room temperature, the obtained brown powder is the CuMoO4 / MnO2 / tourmaline composite precursor;

[0018] 9) Calcinate the CuMoO4 / MnO2 / tourmaline composite precursor to obtain the CuMoO4 / MnO2 / tourmaline heterogeneous catalyst.

[0019] Further, in step 1), the mass ratio of KMnO4 to tourmaline is 1.0 - 3.0 g: 0.4 - 1.2 g.

[0020] Further, in step 2), the temperature of the hydrothermal reaction is 160 - 180 °C, and the time of the hydrothermal reaction is 20 - 24 h.

[0021] Further, in step 4), the drying temperature is 60 - 80 °C and the drying time is 12 - 24 h.

[0022] Further, in step 5), the mass ratio of Cu(NO3)2·3H2O, (NH4)6·Mo7O 24 ·4H2O to the MnO2 / tourmaline composite is 0.6040 - 1.8120 g: 0.4414 - 1.3242 g: 0.2500 - 0.7500 g.

[0023] Further, in step 6), the temperature of the hydrothermal reaction is 150 - 180 °C, and the time of the hydrothermal reaction is 6 - 12 h.

[0024] Further, in step 8), the drying temperature is 60 - 80 °C and the drying time is 12 - 24 h.

[0025] Further, in step 9), the calcination temperature is 400 - 500 °C and the calcination time is 4 - 5 h.

[0026] The heterogeneous catalyst based on the tourmaline composite material prepared by the above method presents an irregular block structure, and the particle size is 0.5 - 2 microns.

[0027] The above heterogeneous catalyst based on the tourmaline composite material can be applied to the photocatalytic degradation of water pollutants by the Fenton-like process. This heterogeneous catalyst can activate PMS under visible light irradiation to construct a photocatalytic Fenton-like system, achieving efficient degradation of tetracycline hydrochloride. The degradation efficiency of the photocatalytic Fenton-like system with a mass ratio of heterogeneous catalyst to PMS of 1:1.2 for tetracycline hydrochloride with a concentration of 50 mg / L can reach 93.48%.

[0028] The beneficial effects of the present invention are as follows:

[0029] 1. This application prepares a heterogenous catalyst using CuMoO4, MnO2, and tourmaline as the main raw materials. As a proven photocatalytic material, CuMoO4 has important application value in water splitting, carbon dioxide reduction, and photocatalytic degradation of pollutants due to its unique crystal structure and excellent photocatalytic activity. However, its wide bandgap and narrow light absorption range affect the photocatalytic efficiency. To compensate for the wide bandgap, this application couples CuMoO4 with a wide bandgap and MnO2 with a narrow bandgap by limiting their composite ratio to prepare a CMT heterojunction with a matched bandgap structure. After the combination, it can effectively adjust the light absorption threshold and energy band structure of the photocatalyst, improve the mobility of photo-generated carriers, reduce the recombination of photo-generated electrons and holes, and correspondingly increase the photocatalytic activity of the two semiconductor materials;

[0030] 2. The heterogenous catalyst disclosed in this application can produce a synergistic effect in the visible light irradiation and PMS activation system, making the catalytic activity of the photocatalytic synergistic PMS activation system higher than that of a single photocatalytic or PMS activation system. Under suitable conditions, it can rapidly degrade tetracycline hydrochloride in water, and the removal efficiency of tetracycline hydrochloride with a concentration of 50 mg / L can reach 93.48%;

[0031] 3. The heterogenous catalyst disclosed in this application is prepared based on tourmaline. Tourmaline is a borate mineral characterized by containing boron, with unique properties such as surface electric field, conductivity, far-infrared radiation, and negative ion release. It can inhibit the recombination of carriers in the photocatalyst and improve the photocatalytic activity of the composite photocatalytic material; the electric field generated by tourmaline can promote the adsorption of pollutants on the catalyst surface, thereby enhancing the photocatalytic degradation of pollutants; tourmaline can also be used as a Fenton-like reagent to activate PMS to promote the generation of active free radicals; under the synergistic effect of photocatalysis and PMS activation, the degradation efficiency of pollutants is finally significantly improved;

[0032] 4. Due to the existence of the [MnO6] octahedral crystal structure, MnO2 has a large specific surface area and a high redox potential, making it have excellent performance in activating peroxymonosulfate (PMS);

[0033] 5. The pollutants oxidized and degraded by using the heterogenous catalyst disclosed in this application are not limited to tetracycline. Pollutants that can be oxidized and degraded through the photo-Fenton reaction can all improve the degradation efficiency by this method, with a wide application range, which helps to broaden the treatment ideas in the field of water purification. Description of the Drawings

[0034] Figure 1 XRD patterns of tourmaline, MnO2, CuMoO4, MT composite, and CMT composite;

[0035] Figure 2Scanning electron microscopy (SEM) images of the prepared samples, where the inset (a) is the SEM image of tourmaline; the inset (b) is the SEM image of the MT composite; the inset (c) is the SEM image of CuMoO4; the inset (d) is the SEM image of the CMT composite;

[0036] Figure 3 FTIR spectra of tourmaline, the MT composite, and the CMT composite;

[0037] Figure 4 XPS spectra of the CMT composite, where the inset (a) is the survey spectrum; the inset (b) is for Cu 2p; the inset (c) is for Mo 3d; the inset (d) is for Mn 2p; the inset (e) is for O 1s; the inset (f) is for Si 2p;

[0038] Figure 5 UV-visible diffuse reflectance spectra of the prepared samples, where the inset (a) is the absorption spectra of tourmaline, MnO2, CuMoO4, and the CMT composite; the inset (b) is the curve of (αhν) n vs. hν;

[0039] Figure 6 Comparison chart of the degradation effects of different reaction systems on tetracycline hydrochloride. Detailed implementation manners

[0040] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Modifications and substitutions made to the methods, steps, or conditions of the present invention without departing from the essence of the present invention all fall within the protection scope of the present invention.

[0041] Example 1: Preparation of the CuMoO4 / MnO2 / tourmaline (CMT) heterogeneous catalyst

[0042] 1) Weigh 1.0 g of KMnO4 and 0.4 g of tourmaline (state: powder, particle size: 0.5 - 2 microns, source: Hebei Province, purity: >95%) (Tourmaline) and disperse them in deionized water. After ultrasonic treatment for 10 min and stirring for 15 min, a suspension A is obtained;

[0043] 2) Transfer the suspension A obtained in step 1) to a reaction kettle and carry out a hydrothermal reaction at 160 °C for 24 h;

[0044] 3) Transfer the product obtained in step 2) to a centrifuge tube and centrifuge it at 10000 rpm for 3 min. Wash it alternately with deionized water and absolute ethanol to obtain a brownish-black precipitate;

[0045] 4) Put the brownish-black precipitate obtained in step 3) into an oven and dry it at 60 °C for 24 h. After cooling to room temperature, the obtained brownish-black powder is the MnO2 / tourmaline composite;

[0046] 5) Weigh 0.6040 g of Cu(NO3)2·3H2O and 0.4414 g of (NH4)6·Mo7O 24 ·4H2O and dissolve them in deionized water, and stir to obtain solution B; weigh 0.2500 g of the MnO2 / tourmaline composite and disperse it into solution B, and stir for 60 min to obtain suspension C;

[0047] 6) Transfer the suspension C obtained in step 5) to a reaction kettle and carry out hydrothermal reaction at 150 °C for 6 h;

[0048] 7) Transfer the product obtained in step 6) to a centrifuge tube, centrifuge at 10000 rpm for 3 min, and wash alternately with deionized water and absolute ethanol to obtain a brown precipitate;

[0049] 8) Put the brown precipitate obtained in step 7) into an oven and dry it at 60 °C for 24 h. After cooling to room temperature, obtain the CuMoO4 / MnO2 / tourmaline composite precursor;

[0050] 9) Place the CuMoO4 / MnO2 / tourmaline composite precursor obtained in step 8) in a muffle furnace and calcine it at 500 °C for 4 h to finally obtain the CuMoO4 / MnO2 / tourmaline heterogeneous catalyst.

[0051] Comparative Example 1. Preparation of MnO2 powder

[0052] Weigh 1.0 g of KMnO4 and dissolve it in deionized water. Stir until dissolved under a magnetic stirrer, transfer it to a reaction kettle, react at 160 °C for 24 h, centrifuge, collect the precipitate in a centrifuge tube, wash alternately with deionized water and absolute ethanol, and place it in an oven at 60 °C to dry for 24 h to obtain MnO2 powder.

[0053] Comparative Example 2. Preparation of CuMoO4 powder

[0054] Weigh 0.6040 g of Cu(NO3)2·3H2O and 0.4414 g of (NH4)6·Mo7O 24 ·4H2O in deionized water, stir magnetically for 60 min, transfer the solution to a reaction kettle, react at 150 °C for 6 h, centrifuge and wash, and place it in an oven at 60 °C to dry for 24 h to obtain the CuMoO4 precursor.

[0055] Place the CuMoO4 precursor in a muffle furnace and calcine it at 500 °C for 4 h to obtain CuMoO4 powder with good crystal phase.

[0056] Comparative Example 3: Preparation of MnO2 / Tourmaline (MT) Composite

[0057] Weigh 1.0 g of KMnO4 and 0.4 g of tourmaline and disperse them in deionized water. After ultrasonic treatment for 10 min and stirring for 15 min, a suspension is obtained; transfer the suspension to a reaction kettle and carry out hydrothermal reaction at 160 °C for 24 h; transfer the obtained product to a centrifuge tube and wash it alternately with deionized water and absolute ethanol to obtain a brownish-black precipitate; place the obtained brownish-black precipitate in an oven and dry it at 60 °C for 24 h. After cooling to room temperature, the prepared brownish-black powder is the MnO2 / tourmaline composite.

[0058] Relevant performance tests:

[0059] 1. Figure 1 Shows the crystallographic characteristics of tourmaline, MnO2, CuMoO4, MT composite and CMT heterogeneous catalyst.

[0060] For tourmaline (JCPDS 70-1877), the characteristic diffraction peaks of tourmaline are located at 13.8°, 17.8°, 19.2°, 21.0°, 22.2°, 25.6°, 30.1°, 34.7°, 44.2°, 47.2°, 50.0°, 55.2°, 57.6° and 63.8°, corresponding to the (101), (021), (300), (211), (220), (012), (122), (051), (152), (342), (612), (063), (550) and (514) crystal planes respectively.

[0061] For MnO2 (JCPDS 80-1098), there are three characteristic diffraction peaks at 12.6°, 25.2° and 37.3°, which are attributed to the (001), (002) and (-111) crystal planes respectively.

[0062] For CuMoO4 (JCPDS 85-1530), the diffraction peaks at 2θ of 9.5°, 13.1°, 14.2°, 15.8°, 16.9°, 19.4°, 22.3°, 23.3°, 23.8°, 24.8°, 26.3°, 26.8°, 28.6°, 29.6°, 32.9° and 34.5° match the (100), (-101), (-110), (101), (1-11), (110), (-102), (0-12), (201), (111), (-202), (-120), (-220), (2-21), (021) and (-1-22) crystal planes respectively.

[0063] The MT composite showed characteristic diffraction peaks of MnO2 and tourmaline, and the CMT composite showed diffraction peaks of CuMoO4, MnO2 and tourmaline, and no impurity peaks appeared in the two composite materials. The XRD characterization results preliminarily showed that Example 1 successfully prepared a CuMoO4 / MnO2 / tourmaline heterogeneous catalyst with a good crystal structure.

[0064] 2. SEM images of tourmaline, MT composite, CuMoO4 and CMT heterojunctions Figure 2 As shown in the (a)-(d) panels. Figure 2 As shown in the middle (a) panel, tourmaline is an irregular block structure. Due to the spontaneous polarization effect, small particles tend to aggregate and adsorb on the surface of large particles. Figure 2 As can be seen in the middle (b) figure, MnO2 nanosheets with a size of 200 to 500 nm are evenly distributed on the tourmaline surface, forming a porous honeycomb structure, which greatly increases the specific surface area and provides more reaction active sites for the catalytic reaction. Figure 2 The middle panel (c) is a scanning electron microscope image of CuMoO4. The particle size of pure CuMoO4 is 100 to 300 nm. Figure 2 The middle panel (d) shows that the CuMoO4 / MnO2 / tourmaline heterojunction is irregular in shape and is composed of tourmaline, MnO2 and CuMoO4.

[0065] 3. Figure 3 This is the FTIR spectrum of tourmaline, MT and CMT composites. Tourmaline has a wavelength of 3573 cm -1 、3487cm -1 and 1632cm -1 There are three peaks at 1246 cm -1 、1061cm -1 and 498cm -1 The peaks at correspond to the stretching vibration of [BO3], ν as (O–Si–O) and δ(Si–O–). At 1030 cm -1 、840cm -1 and 777cm -1 The three stretching vibration peaks detected at 711 cm -1 、648cm -1 and 553cm -1 The peak at is attributed to the characteristic peak of Si–O–Al(Si).

[0066] After modification with MnO2 nanosheets, the MT composite material has a -1 The characteristic peak at 801 cm-1 The signal peak at [885 cm] is attributed to the stretching vibration of Mo–O in CuMoO4. -1 and [936 cm] -1 The characteristic peaks correspond to the vibration of the distorted MoO4 tetrahedron.

[0067] In addition to the characteristic peaks of CuMoO4, the FTIR spectrum of the CMT composite material also includes the characteristic adsorption peaks of tourmaline and the MT complex, demonstrating that the heterogeneous CuMoO4 / MnO2 / tourmaline heterogeneous catalyst was successfully prepared in this application.

[0068] 4. The elemental valence states in the CMT heterogeneous catalyst were studied using XPS spectra. Figure 4 The small figure (a) in [XPS spectrum] is the total XPS elemental spectrum of the CMT heterojunction, indicating that the composite material mainly contains five elements: Cu, Mo, Mn, O, and Si.

[0069] As Figure 4 shown in the small figure (b) in [XPS spectrum], the characteristic peak at 935.5 eV is for Cu 2p 3 / 2 , and the characteristic peak at 955.4 eV corresponds to Cu 2p 1 / 2 , indicating that the valence state of the Cu element in this material is +2. There are two satellite peaks located at 944.0 eV and 963.3 eV, further verifying the existence of Cu 2+ .

[0070] From Figure 4 the small figure (c) in [XPS spectrum], it can be seen that the high-resolution spectrum of Mo 3d with a Mo 6+ valence state has two characteristic peaks at 232.7 eV and 235.8 eV, which correspond to Mo 3d 5 / 2 and Mo 3d 3 / 2 , respectively. The peak at 232.7 eV is attributed to Mo 6+ in CuMoO4, and the peak at 235.8 eV is attributed to Mo 6+ in MoO3.

[0071] The Mn 2p spectrum is split into Mn 2p 3 / 2 (642.7 eV) and Mn 2p 1 / 2 (654.4 eV) ( Figure 4 the small figure (d) in [XPS spectrum]), which corresponds to Mn 4+ in the composite material. The spin-orbit splitting energy of Mn 2p is 11.7 eV, further confirming that the Mn element exists in a 4+ valence state.

[0072] Figure 4The small figure in (e) is the high-resolution spectrum of O 1s. The fitting peaks at 530.6 eV are considered to be Cu-O, Mo-O, and Mn-O-Mn in metal oxides. Another fitting peak at 532.0 eV is attributed to Mn-O-H.

[0073] As Figure 4 shown in the small figure in (f), the Si 2p spectrum shows a characteristic peak at 102.9 eV, which is mainly due to the presence of SiO2 in tourmaline.

[0074] 5. UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS) can illustrate the light absorption characteristics of tourmaline, MnO2, CuMoO4, and CMT heterojunctions ( Figure 5 the small figure in (a)). Pure MnO2 has a strong visible light absorption intensity in the entire visible light region. Compared with MnO2, tourmaline has a poor ability to absorb visible light, and its absorption edge is located at 629 nm. The absorption edge of pure CuMoO4 is located near 585 nm, indicating that it can only absorb solar energy with wavelengths less than 585 nm. In addition, compared with CuMoO4 and tourmaline, the CMT composite shows a wider visible light absorption range and stronger absorption ability, which is attributed to the enhanced photon response ability of MnO2 in this heterojunction, thus improving the photocatalytic performance of the composite.

[0075] According to the Tauc function, the band gap values of tourmaline, MnO2, CuMoO4, and CMT heterojunctions are 1.38 eV, 1.08 eV, 2.01 eV, and 1.49 eV respectively ( Figure 5 the small figure in (b)). It is proved that under the limited composite parameters, coupling the wide-bandgap CuMoO4 and the narrow-bandgap MnO2 to prepare the CMT heterojunction can effectively adjust the light absorption threshold and energy band structure of the composite photocatalyst, improve the light quantum efficiency, realize the rapid separation of photogenerated carriers, and reduce the recombination of electrons and holes.

[0076] 6. Performance test of the photo-Fenton-like system for the degradation of tetracycline hydrochloride

[0077] In this test, tetracycline hydrochloride was used as the model pollutant to study the photo-Fenton-like catalytic reaction activity of the CMT heterojunction. The degradation experiment was carried out in a 100 mL condensation beaker, and the temperature of the reaction system was controlled at 25 °C by using the condensation water circulation. A 300 W xenon lamp equipped with a 420 nm filter was used as the visible light source, and the distance between the xenon lamp and the liquid surface was kept at about 7 cm.

[0078] First, 50 mg of the heterogeneous catalyst and 0.06147 g of PMS were added to the aqueous solution of tetracycline hydrochloride (100 mL, 50 mg / L), and the reaction system was placed in a visible light irradiation environment for degradation performance testing. Every 10 min, 3 mL of the reaction solution was taken into a centrifuge tube and mixed with 1 mL of methanol, and then filtered with a sterile syringe equipped with a 0.22 μm aqueous filter, and then the absorbance was measured at λ max = 356 nm using a double-beam ultraviolet-visible spectrophotometer.

[0079] Figure 6 Figure for comparing the degradation effects of different reaction systems on tetracycline hydrochloride. Tetracycline hydrochloride was selected as the model pollutant to explore the catalytic degradation performance of the CMT heterogeneous catalyst for activating PMS to degrade organic pollutants under visible light irradiation. The degradation of tetracycline hydrochloride by visible light (Vis) irradiation alone was negligible. Due to the presence of limited free radicals, the separate PMS system could achieve a tetracycline hydrochloride removal efficiency of 37.32% within 50 min.

[0080] In addition, the degradation efficiencies of tourmaline / Vis, MT / Vis, and CuMoO4 / Vis systems for tetracycline hydrochloride were 18.59%, 34.15%, and 51.84% respectively. After adding PMS to the above catalytic systems to form tourmaline / PMS / Vis, MT / PMS / Vis, and CuMoO4 / PMS / Vis systems, the degradation efficiencies of tetracycline hydrochloride were significantly improved, reaching 75.16%, 80.18%, and 64.61% respectively, which can be attributed to the synergistic effect of photocatalysis and PMS activation.

[0081] Under the action of visible light irradiation or PMS activation, the degradation efficiencies of the CMT / Vis and CMT / PMS systems for tetracycline hydrochloride reached 44.49% and 76.51% respectively, indicating that CMT, as a heterogeneous composite material, has good photocatalytic performance and PMS activation ability.

[0082] Under the synergistic effect of photocatalysis and PMS activation, the removal efficiency of the CMT / PMS / Vis system for 50 mg / L of tetracycline hydrochloride was further improved, and the removal rate reached 93.48%, indicating that both photocatalysis and PMS activation play crucial roles in the process of CMT degrading pollutants.

[0083] The above shows and describes the basic principles, main features, and advantages of the present invention. However, the above are only specific embodiments of the present invention, and the technical features of the present invention are not limited thereto. Any other embodiments obtained by those skilled in the art without departing from the technical solution of the present invention should be covered within the patent scope of the present invention.

Claims

1. A method for preparing a heterogeneous catalyst based on a tourmaline composite material, characterized in that, The steps include: 1) Weigh KMnO4 and tourmaline and disperse them in deionized water, and obtain suspension A after ultrasonication and stirring; 2) transferring the suspension A obtained in step 1) to a reactor for hydrothermal reaction; 3) centrifuging the product obtained in step 2) and washing it to obtain a brown-black precipitate; 4) drying the precipitate obtained in step 3) and cooling it to room temperature, and the obtained brown-black powder is a MnO2 / tourmaline composite; 5) Weigh Cu(NO3)2·3H2O and (NH4)6·Mo7O 24 ·4H2O and dissolve them in deionized water, stir to obtain solution B; weigh the MnO2 / tourmaline composite and disperse it into solution B, stir to obtain suspension C; 6) Transferring the suspension C to a reactor for hydrothermal reaction; 7) centrifuging the product obtained in step 6) and washing it to obtain a brown precipitate; 8) drying the brown precipitate obtained in step 7) and cooling it to room temperature. The obtained brown powder is a CuMoO4 / MnO2 / tourmaline composite precursor; 9) calcining the CuMoO4 / MnO2 / tourmaline composite precursor to obtain a CuMoO4 / MnO2 / tourmaline heterogeneous catalyst.

2. The preparation method of the heterogeneous catalyst based on the tourmaline composite material according to claim 1, wherein, In step 1), the mass ratio of KMnO4 to tourmaline is 1.0-3.0 g:0.4-1.2 g.

3. The preparation method of the heterogeneous catalyst based on the tourmaline composite material according to claim 1, characterized in that, In step 2), the temperature of the hydrothermal reaction is 160-180° C. and the hydrothermal reaction time is 20-24 h.

4. The preparation method of the heterogeneous catalyst based on the tourmaline composite material according to claim 1, characterized in that, In step 4), the drying temperature is 60-80° C. and the drying time is 12-24 hours.

5. The preparation method of the heterogeneous catalyst based on the tourmaline composite material according to claim 1, characterized in that, In step 5), the mass ratio of Cu(NO3)2·3H2O, (NH4)6·Mo7O 24 ·4H2O and the MnO2 / tourmaline composite is 0.6040 - 1.8120 g: 0.4414 - 1.3242 g: 0.2500 - 0.7500 g.

6. The preparation method of the heterogeneous catalyst based on tourmaline composite material according to claim 1, characterized in that, In step 6), the temperature of the hydrothermal reaction is 150-180° C., and the time of the hydrothermal reaction is 6-12 hours.

7. The preparation method of the heterogeneous catalyst based on the tourmaline composite material according to claim 1, characterized in that, In step 8), the drying temperature is 60 to 80° C. and the drying time is 12 to 24 hours.

8. The preparation method of the heterogeneous catalyst based on the tourmaline composite material according to claim 1, characterized in that, In step 9), the calcination temperature is 400-500° C. and the calcination time is 4-5 hours.

9. A heterogeneous catalyst based on tourmaline composite materials, characterized in that, The catalyst is prepared by the method for preparing a heterogeneous catalyst based on a tourmaline composite material according to any one of claims 1 to 8. The heterogeneous catalyst is an irregular block structure with a particle size of 0.5 to 2 microns.

10. Use of the heterogeneous catalyst based on tourmaline composite material according to claim 9 in catalytic degradation of water pollutants, characterized in that, The heterogeneous catalyst can activate PMS under visible light irradiation to construct a photo-Fenton-like system, thereby achieving efficient degradation of tetracycline hydrochloride. The photo-Fenton-like system with a mass ratio of the heterogeneous catalyst to PMS of 1:1.2 can achieve a degradation efficiency of 93.48% for tetracycline hydrochloride at a concentration of 50 mg / L.

Citation Information

Patent Citations

  • Preparation method of bismuth molybdate-coated tourmaline composite photocatalyst

    CN111450822A

  • Visible-light-driven photocatalyst based on mineral composite material and preparation method thereof

    CN113145134A